Moral value in serial cartoon Upin and Ipin English version - Indah Muzdalifah; Elvira Asril; Susi Handayani (Universitas Lancang Kuning, 2020)
There are many technology-based media that can use in learning English. One of them is the English version of Upin Ipin which can download from YouTube. The purpose of this study is to describe the ability of students to study, analyze and translate moral values ​​contained in each episode of the Upin Ipin cartoon series. The research method taken is a qualitative method in which the ability of students to describe the value of moral tests using tests and ruptures. The results of this study were the first of 31 students 22 people were able to explain moral values ​​well, and 3 people were excellent